Comparison of pharmacognosy between Salvia evansiana and S. miltiorrhiza - CAI Wen-guo; LIU Zeng-yu; ZHONG Guo-cheng; WANG Meng; ZHANG Li (浙江大学学报. 农业与生命科学版)
Pharmacognostic characteristics between Salviaev ansiana and S. miltiorrhiza were assessed based on morphologic identification, microscopic identification, thin-layer chromatography (TLC) and high performance liquid chromatography (HPLC). The results demonstrated that, compared with S. miltiorrhiz a, S. ev ansiana showed some differences in morphological traits of plants height, foliage and flower, etc, and there was no sclereid but larger vessels in its root powder. On the TLC plate, there were different numbers of spots on the extracts of the two species. HPLC analysis showed that the content of tanshinone Ⅱ A in S. ev ansiana was 0.0812%, which did not reach the amount stated by The Pharmacopoeia of the People's Republic of China (2005), whereas Danshensu was not detected. Therefore, S. evansiana and S. miltiorrhiza can be clearly distinguished by the four methods mentioned above. The results over indicate also that S. evansiana may not be used as S. miltiorrhiza.